New Arrangements to Borrow : Proposed Renewal of and Modifications to the NAB Decision. (Policy Papers; Policy Paper ;, 2016)
The Fund's decision on the New Arrangements to Borrow (the 'NAB'), as amended, (the 'NAB Decision') is subject to renewals not later than 12 months before the end of each NAB period, with the current period set to expire on November 16, 2017. The NAB Decision was last renewed for a five-year period in November 2012. Pursuant to paragraph 19(a) of the NAB Decision, the Executive Board is to take a decision on the renewal no later than twelve months before the end of the NAB Decision, id est, by November 16, 2016.1 Once a decision on renewal is taken, the new NAB period would become effective on November 17, 2017. In renewing the NAB Decision, the Fund and NAB participants are to review the functioning of the NAB Decision and, in particular, the experience with the procedures for activation. Modifications of the NAB Decision could be made at the time of renewal.